Mobile teledermatology in diagnosis and management of two tinea incognito cases at a primary health center of semi-urban Kathmandu - Shrestha, Shumneva; Yadav, Randhir Sagar; Baral, Suwash; Shrestha, Dwarika Prasad (Journal of Chitwan Medical College, 2018)
Skin diseases are among leading health problems in Nepal. Fungal infections are the tenth most common reason of OPD visits in Nepal. Due to inappropriate or inadequate treatment, clinically modified tinea infections known as tinea incognito is very common. There is no dermatological care in the primary health centers. The medical officers in these centers have inadequate training to manage skin diseases, while the health workers have no training. Most dermatologists are based in tertiary hospitals and medical colleges of bigger cities. Mobile teledermatology is an innovative method to provide dermatological care to the health centers where there are no dermatologists. It is equally effective means of on-site training for the medical officers. We report two cases of tinea incognito, which were treated by a medical officer at a primary health center with the aid of mobile teledermatology consultation provided by a dermatologist.